EFFECTIVENESS OF GIVING DEEP RELAXATION TO REDUCE PAIN IN HYPERTENSION PATIENTS IN EDELWEIS ROOM DOWN, KARDINAH TEGAL HOSPITAL - Slamet Edi Susanto; Tophan Heri Wibowo (Sekolah Tinggi Pariwisata Mataram, 2022)
Background: Hypertension or high blood pressure affects almost all groups of people around the world. One of the symptoms that appear in hypertension is acute pain. Good care is an important factor in determining the patient's recovery Objective: to analyze cases managed by hypertensive patients with acute pain in Mrs. T at Kardinah Hospital, Tegal. Methodology: The method used in this research is descriptive using a case study approach at Kardinah Hospital Tegal. Results: The results of the assessment and data analysis formulate a nursing diagnosis of acute pain related to biological injury. Based on the problem of acute pain with non-pharmacological intervention of deep breath relaxation to decrease pain intensity, it was found that there was an improvement or decrease in pain scale after providing nursing care for 3 days.